Halal Industry: Are The Businesses Fully Awake? - Norailis Ab Wahab; Kamarubahrin, A. F. (Universiti Sains Islam Malaysia, 2024)
Nowadays, organisations are involved in intense competition to sell their products and services globally. The current target market covers nearly every country in the world, including Islamic countries. For example, Japan and Australia are putting great effort into catering to a rising number of Muslim clients by increasing their investment and expertise in halal products and services. Their aim is to attract the attention of the growing Muslim population to add a billion by 2050. Halal products include food and beverages, personal care, cosmetics, pharmaceuticals and health products. Meanwhile, halal services comprise areas such as Islamic finance, takaful, travel, education and healthcare. Subsectors such as media, consulting, events, online services, software development, logical services and lab testing can also benefit from the growth of the halal sector as a whole. The authors will attempt to achieve two objectives in this paper: (i) to examine current literature and (ii) to determine the success factors of and issues faced by halal businesses. The Malaysian government's intention is not only to support the halal industry in terms of complying with regulations set by the authorities and obtaining the relevant certification; the output must also meet international standards to supply consistently high-quality products and services to win customers hearts.